Research of thixotropy of emulsion sauce with buttermilk concentrate during storage - Юдіна, Тетяна Іллівна (Eastern-European Journal of Enterprise Technologies, 2015)
The paper provides the technology of the emulsion sauce (ES) using dry milk-protein concentrate (DMPC) with buttermilk with the fat content of 30%, which allows to expand the range of emulsion sauces with high nutritional and biological value, rationally use protein-carbohydrate raw milk. Thixotropic properties of the developed emulsion sauce using DMPC with buttermilk were investigated. Based on rheological studies, it was found that the emulsion sauce does not lose the ability to restore the structure and has thixotropic properties after 24, 72 hours and 90 days of storage at 4±2°C. The equations of effective viscosity of the emulsion sauce hysteresis loop after 24, 48 and 72 hours of storage were given. The results confirm the ES shelf life, previously established based on microbiological studies - 72 hours without preservative and 90 days with the preservative. With the specified shelf life, the developed emulsion sauce using dry milk-protein concentrate with buttermilk is within excellent quality.